Melatonin supports alendronate in preserving bone matrix and prevents gastric inflammation in ovariectomized rats - YEGEN, BERRAK; ERCAN, FERİHA; AKKİPRİK, MUSTAFA; KAYA, ÖZLEM TUĞÇE (WILEY, 2019)
The anti-catabolic bisphosphonate alendronate is considered as the first-line medical treatment in post-menopausal osteoporosis; but several side effects, including gastric mucosal injury, are associated with its use. The aim was to elucidate whether combined treatment with melatonin plus alendronate would be more advantageous in the maintenance of bone and the prevention of gastric side effects. Under anaesthesia, female Sprague-Dawley rats underwent bilateral ovariectomy (OVX), while control group had sham surgery. Four weeks after the surgery, OVX rats were treated with saline, melatonin (25 mu g/mL/d), alendronate (70 mu g/kg/wk), melatonin + alendronate, melatonin + melatonin receptor antagonist (luzindole, 10 mu g/kg/d) or alendronate + melatonin + luzindole for 8 weeks. Rats were euthanized at the end of 12th week. Runx2 expression, apoptotic cells, and trabecular thickness were evaluated in tibiae, while gastric tissues were analysed for oxidative injury parameters. In all OVX groups, Runx2 expression was depressed. Saline-treated OVX group presented an extreme decrease in calcified area in opposition to melatonin- or alendronate-treated groups, while the bones in alendronate + melatonin-treated group were similar to those of the sham-operated group. Concomitant with the improvements examined histologically in bone tissues, quantitative TUNEL (+) cells were similarly lower in alendronate- or melatonin-treated groups. Oxidative gastric damage was increased in saline- or alendronate-treated groups, which were depressed in the presence of melatonin. Although melatonin and alendronate exerted similar supportive effects on the maintenance of bone mass, melatonin may have a more advantageous impact by protecting against OVX-induced gastric injury, which was aggravated by alendronate use. Highlights Our results demonstrate that alendronate and melatonin had similar supportive effects on the maintenance of bone mass, while melatonin prevented the gastric side effects of alendronate, making this combination an advisable therapeutic approach in the treatment of menopausal osteoporosis.
Keywords: alendronate; gastric injury; melatonin; osteoporosis; post-menopausal; MESENCHYMAL STEM-CELLS; INJURY; DIFFERENTIATION; EXPRESSION